Determining the diagnostic cut-off on the Chinese version of severity of dependence scale for DSM-5 stimulant use disorder - Chung, Albert Kar Kin; Leung, Welton; Tse, Cheuk Yin (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the psychometric properties of the Chinese version of the Severity of Dependence Scale for stimulant (C-SDS-S) in screening for the DSM-5-defined Stimulant Use Disorder (SUD).DesignRetrospective chart review.MethodsA total of 227 Chinese-speaking stimulant (methamphetamine and cocaine) users were identified from four previous studies conducted in Hong Kong. Their demographic data, frequency of stimulant use within the past 30 days, scorings for C-SDS-S and the severity of SUD at baseline were extracted and synthesized. In addition, test-retest reliability of C-SDS-S was assessed in 101 subjects who reported C-SDS-S scorings 4 weeks after baseline.FindingsThe C-SDS-S demonstrated an acceptable internal consistency with a Cronbach’s alpha of 0.736. C-SDS-S scorings were associated with the severity of SUD (ρ = 0.292, p <.001) and with the frequency of stimulant use within the past 30 days (ρ = 0.196, p = .003). All items loaded into one factor which accounted for 50.21% of the variance. Receiver operating characteristic analysis demonstrated that a C-SDS-S cut-off score of ≥ 5 provided optimal discrimination for moderate-to-severe SUD among Chinese-speaking individuals using stimulants. Total scores and individual items of the C-SDS-S demonstrated fair to moderate 30-day test-retest reliability (intraclass correlation coefficient = 0.49; weighted Kappa’s = 0.25-0.46).ConclusionThe C-SDS-S is a valid and reliable screening instrument to identify stimulant users with DSM-5 defined moderate-to-severe SUD in the Chinese-speaking population.